Behavioral factors associated with patients' non-attendance: A retrospective study in an outpatient specialty clinic at a women's and children's hospital in Singapore - TANG, Yue (Institutional Knowledge at Singapore Management University, 2024)
Background: This study aimed to identify behavioral factors that affect patient attendance in outpatient clinics, especially those related to rescheduling. Methods: A retrospective study was conducted on 20,386 appointment records for 6,252 patients in an outpatient specialty clinic at a women’s and children’s hospital in Singapore over 34 months (January 2012–October 2014). Multivariate logistic regression was used to analyze the influence of independent variables on appointment no-shows. Results: The average no-show rate of the study population was 28.87%. Patient historical behaviors were significantly associated with appointment attendance. In particular, a larger number of previous visits, more historical no-shows, more historical rescheduling events initiated by patients, and more reschedulings initiated by the clinic for the current appointment were positively associated with no-shows. Notably, the number of previous visits was found to exhibit a significantly diminishing marginal effect on no-show rates. Further analyses suggested that for appointments rescheduled by the clinic, subsequent rescheduling by patients was associated with a reduced risk of no-shows. Conclusions: No-shows were more common in patients who missed more historical appointments or had their appointments rescheduled more frequently. Encouraging patients to reschedule their own appointments could be an effective measure to reduce no-shows. However, the benefit of patient-rescheduling decreased if patients rescheduled appointments repeatedly.